Paradigms and Epistemology of Research: Positivist, Interpretive, Critical, and Islamization of Knowledge - Dertha Mukhtar; Zulfani Sesmiarni; Ramadhoni Aulia Gusli (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This article discusses research paradigms and epistemology in the context of scientific development, particularly from the perspective of Islamic scholarship. Knowledge evolves through various paradigms that shape researchers’ views of reality, research objects, methods, and purposes. The three main paradigms commonly used are positivistic, interpretive, and critical. In addition, within the Islamic intellectual tradition, the concept of the Islamization of knowledge emerges as an effort to integrate revelation, reason, and empirical reality. The method used in this study is library research with a descriptive-critical analysis approach. The findings indicate that each paradigm possesses distinct characteristics, orientations, and objectives, yet they complement one another. The paradigm of the Islamization of knowledge serves as an integrative framework that offers ethical, spiritual, and beneficial dimensions to contemporary scientific research.